The information-seeking process of blind and visually impaired Grade 12 learners in selected South African schools for the blind - Hendrikz, Francois (Library and Information Studies Centre (LISC), 2021)
All people seek information for various reasons sometime during their lifetime. How this process has been researched and documented by various researchers is covered in this thesis, showing how the insights and lessons from various Information Seeking Models in the literature have informed and enriched this study. These models provide a good understanding of the study field and frameworks to explain the different elements of the information seeking process. All available Information Seeking Models, however, are developed based on the assumption that information seeking is performed by people with sight. How applicable these Information Seeking Models are for people who are blind and/or visually impaired is not addressed in the research. There are a number of different realities for a blind and visually impaired person seeking information, e.g. the accessibility of the technology to access the information, the accessibility of the information once it is located, the availability of technologies to assist the blind and visually impaired person to enable him/her to seek information, the availability of other people to assist the blind and visually impaired person during the information seeking process are just some of the challenges not addressed by existing Information Seeking Models. The purpose of this study is therefore to give an overview of existing Information Seeking Models and then to focus on the two leading researchers in the field, i.e. C. Kuhlthau and T.D. Wilson. These models of the information seeking process were contextualised and assessed in relation with the information needs model of N. Moore who researched the information needs of blind and visually impaired people. Based on the work of the three researchers a survey instrument was developed to determine the information seeking process of Grade 12 learners at five South African Schools for the Blind. Since Grade 12 learners must decide about their future, after completing school, it was decided to research how Grade 12 learners seek information to assist them to decide about tertiary studies or work options. The study included learners who had not yet started the information seeking process in this regard. A research instrument was designed to collect data to investigate the information seeking processes of the Grade 12 learners in order to assess the extent to which they correlated with the Information Seeking Models of Kuhlthau (1991) and Wilson (1999). The qualitative research method was followed in this study which was located in a constructivist paradigm. Interviews were conducted with 43 learners at the five schools for the blind representing the total population of Grade 12 learners registered at the selected schools. The literature confirms that low population sizes are customary when researching blind and visually impaired people. Face-to-face interviews were conducted at the five schools. The findings of the interviews were analysed through a framework analysis. Thereafter, a gap analysis was conducted to determine to what extent the findings correlated to or differed from the Information Seeking Models. From this analysis seven components were identified as part of the design of the Inclusive Information Seeking Model applicable to blind and visually impaired Grade 12 learners, a major outcome of the study. A broader application of the model is suggested. This Inclusive Information Seeking Model will raise awareness and assist people working in an information environment to make the necessary provisions, to ensure that the information seeking process for blind and visually impaired people is as successful as possible with available resources.